TNF-α Regulates Natriuretic Peptides and Aquaporins in Human Bronchial Epithelial Cells BEAS-2B - Letizia Mezzasoma; Lucio Cagini; Cinzia Antognelli; Francesco Puma; Eugenio Pacifico; Vincenzo Nicola Talesa (Hindawi Limited, 2013)
Postoperative-fluid retention is a severe complication frequently reported in patients undergoing major surgical procedures. The complex network of molecules involved in such a severe surgery-induced condition remains poorly understood. Inflammation has been proposed among the various causes of fluid retention. Since TNF-α is one of the main proinflammatory cytokine initially released after major surgery, it is reasonable to assume its involvement in fluid overload. Here, we showed that TNF-α selectively regulates key molecules involved in fluids balance, such as natriuretic peptides (NPs) and aquaporins, in human bronchial epithelial cells BEAS-2B. In particular, we found that TNF-α induced a decrease of arial natriuretic peptide, natriuretic peptide receptor-1, aquaporin-1 and aquaporin-5 and an increase of brain natriuretic peptide with a different involvement of nuclear factor-κB and mitogen-activated protein kinases signaling pathway activation. Moreover, the observed changes in NPs expression, demonstrate inflammation as an additional cause of brain natriuretic peptide elevation, adding an important piece of information in the novel area of study regarding NPs and inflammation. Finally, we suggest that inflammation is one of the mechanisms of Aquaporin-1 and aquaporin-5 expression regulation. Therefore, in this exploratory study, we speculate that TNF-α might be involved in postoperative-fluid retention related to major surgery.